Does microfinance program innovation reduce income inequality? Cross-country and panel data analysis - Kamel Bel Hadj Miled; Moheddine Younsi; Monia Landolsi (Journal of Innovation and Entrepreneurship, 2022)
This paper uses cross-country and panel data set to test the significance of microfinance on income inequality reduction at the macro level for a sample of 57 developing countries for the periods 2000-2006 and 2007-2013. This study adopts panel data methodologies, such as ordinary least square (OLS), pooled ordinary least square (POLS) and instrumental variables (IV) estimations to overcome the endogeneity problems among the variables. Empirical results show that countries with higher MFIs' gross loan portfolio per capita tend to have lower income inequality, which confirm the beneficial outcome of microfinance in reducing inequality at the macro level. Moreover, our results suggest that microfinance loans can lead to improve the relative income position of the poor in developing countries, albeit slowly. Our findings have relevant recommendations to policymakers, as they could generate suitable strategies to consider microfinance institutions as a more popular tool for fighting against both poverty and inequality.
Keywords: C31; G21; I32; O15; 650; Income inequality; Instrumental variables; Loan portfolio; Macro-level analysis; Microfinance